Interaction of the motor protein SecA and the bacterial protein translocation channel SecYEG in the absence of ATP. Issue 8 (3rd July 2020) - Winkler, Klemens; Karner, Andreas; Horner, Andreas; Hannesschlaeger, Christof; Knyazev, Denis; Siligan, Christine; Zimmermann, Mirjam; Kuttner, Roland; Pohl, Peter; Preiner, Johannes
Abstract : The SecA–SecYEG complex is stable in the absence of nucleotides due to a dual recognition mechanism. Abstract : Translocation of many secretory proteins through the bacterial plasma membrane is facilitated by a complex of the SecYEG channel with the motor protein SecA. The ATP-free complex is unstable in detergent, raising the question how SecA may perform several rounds of ATP hydrolysis without being released from the membrane embedded SecYEG. Here we show that dual recognition of (i) SecYEG and (ii) vicinal acidic lipids confers an apparent nanomolar affinity. High-speed atomic force microscopy visualizes the complexes between monomeric SecA and SecYEG as being stable for tens of seconds. These long-lasting events and complementary shorter ones both give rise to single ion channel openings of equal duration. Furthermore, luminescence resonance energy transfer reveals two conformations of the SecYEG–SecA complex that differ in the protrusion depth of SecA's two-helix finger into SecYEG's aqueous channel. Such movement of the finger is in line with the power stroke mechanism of protein translocation.